Epidemiology of multiple sclerosis in Finland with the emphasis on hospitalization and infection-related admissions - Pirttisalo, Anna-Leena (fi=Turun yliopisto|en=University of Turku|, 2021)
Finland is a high-risk region for multiple sclerosis (MS) and there are marked regional differences in the epidemiology of MS in different parts of the country. Though the prevalence of MS is increasing worldwide, fortunately its treatment has developed considerably during recent decades. MS patients use health services more than the general population and carry an increased risk of suffering infections, which could potentially be further increased by new disease modifying therapies (DMTs). The aim of this thesis was to evaluate regional differences in MS epidemiology in Finland by reviewing previous epidemiological studies of MS and introducing new epidemiological data from the western, southwestern and eastern regions of Finland. In order to assess the changing burden of MS on the health system and the effects of new DMTs, another aim was to investigate trends in hospital admission rates of MS patients and the role of infections in MS-related hospital admissions in Finland and to identify those factors predisposing to infection-related MS admissions. Data were derived from registers of hospitals and National Institute for Health and Welfare. We estimated an age-standardized MS prevalence of 251/100,000 in Southwest Finland and 150/100,000 in eastern North Karelia in 2016. The highest MS prevalence of 288/100,000 was observed in South Ostrobothnia in 2007. The age-standardized MS incidence was 9.2/100,000 person-years in Southwest Finland and 6.5/100,000 personyears in North Karelia in 2012–2016. MS-related hospital admissions declined by 4.6% annually representing an annual aggregate reduction of cost of hospital admissions by 51% in Finland from 2004 to 2014. During the second study period 2009–2018, which focused on Southwest Finland, there were declines in both the annual number of MS-related hospital admissions and the number of infection-related admissions. Patients with infection-related admissions were older and more often male, had longer disease durations, more disability, more often a progressive disease and more comorbidities. DMTs were used less often by patients with infection admissions. Our results confirmed clear regional differences of MS epidemiology in Finland with the highest epidemiological figures found in western and southwestern hospital districts. Stable increase in MS prevalence was observed over five decades while incidence has increased only since 1990s. Hospital admissions of MS patients declined during the study periods, a time period coinciding with an increase in the use of DMTs. Infection-related admissions lasted longer and had increased in-hospital mortality emphasizing the importance of the prevention of infections. The association of these admissions with advanced disease and the lesser use of DMTs underline the significance of preventing disability progression in infection prevention in MS.

MS-taudin epidemiologia Suomessa – sairaalahoitoon ja infektioihin painottuvia tutkimuksia Suomi kuuluu multippeliskleroosin (MS) korkean riskin alueeseen ja maassamme on todettu alueellisia eroja taudin epidemiologiassa. MS-taudin esiintyvyys kasvaa maailmanlaajuisesti, mutta myös taudin lääkehoito on kehittynyt nopeasti viimeisten vuosikymmenten aikana. MS-potilaat käyttävät runsaasti terveydenhuollon palveluita ja heillä on kohonnut infektioriski, jota uudet lääkkeet entisestään saattavat lisätä. Tämän väitöskirjatyön tavoitteena oli tutkia aiempaa tarkemmin MS-taudin epidemiologian alueellisia eroja Suomessa tarkastelemalla aiempia epidemiologisia tutkimuksia ja selvittämällä uusia epidemiologisia lukuja Itä-, Länsi- ja Varsinais- Suomessa. Jotta MS-taudin aiheuttamasta terveydenhuollon kuormituksesta ja uusien lääkehoitojen vaikutuksista saataisiin uutta tietoa, toisena tavoitteena oli tutkia MSpotilaiden sairaalahoitojaksojen kehitystä Suomessa ja infektioiden osuutta näiden joukossa sekä tunnistaa sairaalahoitoa vaativille infektioille altistavia tekijöitä Varsinais-Suomessa. Tiedot haettiin sairaaloiden ja Terveyden ja hyvinvoinnin laitoksen rekistereistä. MS-taudin ikävakioitu esiintyvyys oli vuonna 2016 Varsinais-Suomessa 251/100,000 ja Pohjois-Karjalassa 150/100,000. Korkein esiintyvyys oli 288/100,000 ja se todettiin Etelä-Pohjanmaalla vuonna 2007. Ikävakioitu ilmaantuvuus oli 9.2/100,000 henkilövuotta Varsinais-Suomessa ja 6.5/100,000 henkilövuotta Pohjois-Karjalassa ajanjaksolla 2012–2016. MS-potilaiden sairaalahoitojaksot vähenivät Suomessa ensimmäisen tutkimusjakson (2004–2014) aikana 4.6% vuodessa ja sairaalahoitojaksoihin liittyvät vuosittaiset kokonaiskustannukset vähenivät tutkimusjakson aikana 51%. Varsinais-Suomessa sekä kaikki MS-potilaiden sairaalahoitojaksot että infektioihin liittyvät hoitojaksot vähenivät ajanjaksolla 2009- 2018. Infektion vuoksi sairaalaan joutuneet potilaat olivat vanhempia, pidempään MStautia sairastaneita ja useammin miehiä. Lisäksi heillä oli useammin etenevä MS-tauti sekä enemmän invaliditeettiä ja liitännäissairauksia verrattuna alueen muihin MSpotilaisiin. Verrokkipotilailla oli käytössä MS-taudin lääkehoito useammin kuin infektion vuoksi sairaalahoitoon joutuneilla potilailla. Tutkimuksemme vahvisti, että Suomessa on merkittäviä alueellisia eroja MS-taudin epidemiologiassa ja taudin esiintyvyys on korkea Suomen länsi- ja lounaisosissa. MS-taudin esiintyvyys on noussut tasaisesti 50 vuoden aikana, mutta ilmaantuvuus on noussut vasta 1990-luvulta lähtien. MS-potilaiden sairaalahoitojaksot vähenivät tutkimusjaksojen aikana samanaikaisesti MS-taudin lääkehoidon yleistymisen kanssa. Infektioon liittyvät hoitojaksot olivat muita hoitojaksoja pidempiä ja sairaalakuolleisuus oli niihin liittyen korkeampi osoittaen infektioiden ehkäisyn tärkeyden. Infektioon liittyvien hoitojaksojen yhteys edenneeseen MS-tautiin ja vähäisempään MS-taudin lääkehoidon käyttöön korostaa taudin tehokkaan hoidon ja potilaiden hyvän toimintakyvyn merkitystä myös infektioiden ehkäisyssä.